Agriculture in the peasant sector of Sri Lanka - Samarasinghe, S. W. R. de A. (Ceylon Studies Seminar, 1977)
On small scale cultivation of crops; comprises a selection of papers presented at the Conference on Agriculture in the Economic Development of Sri Lanka, Peradeniya, 1974, and contributed articles.